EXPLORING ACADEMIC PERFORMANCE: A COMPARATIVE STUDY OF THARU AND NON-THARU STUDENTS IN BIHAR - Srivastava, Rekha; Gupta, Rajnish Kumar; Sunita Kumari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the academic achievement of Tharu and Non-Tharu adolescents in the Bagaha (sub division of west Champa ran) Bihar, with a particular focus on gender differences and tribal identity. The educational landscape in India is marked by significant disparities, especially among marginalized communities, where socio-economic factors and cultural influences play crucial roles in shaping academic outcomes. This paper aims to explore the academic performance of Tharu and non-Tharu adolescents’ students of Bagaha (sub division of west Champaran) Bihar. Sample consisted of 400 adolescent’s students randomly selected from the school. Academic achievement was obtained from the schools. Gender wise and category wise comparisons were done using, Mean, S.D. and independent t-test. The results indicate that Tharu students, despite facing cultural and infrastructural challenges, perform relatively well compared to non-Tharu students. Additionally, female adolescents consistently outperform their male counterparts in both tribal and non-tribal categories. This finding aligns with existing literature that suggests gender dynamics significantly impact educational performance, with girls often exhibiting higher academic motivation and support. Furthermore, the study reveals a substantial difference in academic achievement between tribal male and female students, highlighting the need for targeted interventions that address the unique challenges faced by tribal communities.By contributing to the understanding of educational disparities in the Bagaha, this research underscores the importance of inclusive educational policies and culturally relevant curricula. The findings call for increased community engagement and support systems to enhance academic outcomes for all students, particularly those from marginalized backgrounds. Ultimately, this study aims to inform policymakers and educators about the necessity of addressing the intersectionality of gender and tribal identity in educational planning and implementation.